PEMAHAMAN MAHASISWA PGSD TENTANG KONSEP DASAR IPS MELALUI PENDEKATAN KELOMPOK - Dhea Amanda Alfa Rizki; Annisa Humaila; Faisal Chan; Silvina Noviyanti (Jurnal Tunas Pendidikan, 2024)
Primary School Teacher Education (PGSD) plays a key role in shaping prospective teachers' understanding of Social Sciences (IPS). The complexity of social studies material and its strategic role in basic education requires increased understanding of PGSD students. With diverse backgrounds, a learning approach is needed that integrates this diversity. A group approach is considered a potential solution to achieve these goals. The formation of groups, based on similar backgrounds or interests, is expected to create a focused and relevant discussion environment. This research explores the extent to which group formation and application of a group approach improves PGSD students' understanding of basic social studies concepts. Learning through groups stimulates the application of concepts in practical situations. Group discussions give students the opportunity to link theory with direct experience through collaborative projects. The use of various learning resources, such as books, articles, videos and online learning, is integral in supporting student understanding. This research also investigates meetings with social studies experts to improve PGSD students' understanding. Expert involvement is expected to provide additional insights and in-depth perspectives, helping students develop a comprehensive understanding of basic social studies concepts. Through individual and group reflection, this research observes the internalization of understanding of PGSD students. Individual coaching sessions help students overcome difficulties during learning. It is hoped that the results of this research will provide new insights and make a significant contribution to increasing PGSD students' understanding of basic social studies concepts through a group approach. The research method used is a qualitative approach with case studies, carried out at PGSD Jambi University for the 2022/2023 academic year. The increase in student understanding was seen to be significant after implementing the group approach, indicating that this method can be effective in improving the quality of teacher education and creating a deep and relevant understanding of basic social studies concepts.